A Decision Aid to Promote Appropriate Colorectal Cancer Screening among Older Adults: A Randomized Controlled Trial. (July 2018) - Lewis, Carmen L.; Kistler, Christine E.; Dalton, Alexandra F.; Morris, Carolyn; Ferrari, Renée; Barclay, Colleen; Brewer, Noel T.; Dolor, Rowena; Harris, Russell; Vu, Maihan; Golin, Carol E.
Background. Concerns have been raised about both over- and underutilization of colorectal cancer (CRC) screening in older patients and the need to align screening behavior with likelihood of net benefit.Objective. The purpose of this study was to test a novel use of a patient decision aid (PtDA) to promote appropriate CRC screening in older adults.Methods. A total of 424 patients ages 70 to 84 y who were not up to date with CRC screening participated in a double-blinded randomized controlled trial of a PtDA targeted to older adults making decisions about whether to undergo CRC screening from March 2012 to February 2015.Intervention. Patients were randomized to a targeted PtDA or an attention control. The PtDA was designed to facilitate individualized decision making—helping patients understand the potential risks, benefits, and uncertainties of CRC screening given advanced age, health state, preferences, and values.Outcomes. Two composite outcomes, appropriate CRC screening behavior 6 mo after the index visit and appropriate screening intent immediately after the visit, were defined as completed screening or intent for patients in good health, discussion about screening with their provider for patients in intermediate health, and no screening or intent for patients in poor health. Health state was determined by age and Charlson Comorbidity Index.Results. Four hundred twelve (97%) and 421 (99%) patients were analyzed for the primary and secondary outcomes, respectively. Appropriate screening behavior at 6 mo was higher in the intervention group (55% v. 45%, P = 0.023) as was appropriate screening intent following the provider visit (61% v. 47%, P = 0.003).Limitations. The study took place in a single geographic region. The appropriate CRC screening classification system used in this study has not been formally validated.Conclusions. A PtDA for older adults promoted appropriate CRC screening behavior and intent. Trial Registration: Clinicaltrials.gov, registration number NCT01575990.https://clinicaltrials.gov/ct2/show/NCT01575990?term=epic-d&rank=1